Improving The Mastery Of English Vocabularyof Grade X Students Through The Application Of Word Chain Games At Ma Muhammadiyah Unggulan Gorontalo - Akase, Sastin; Marina Pakaja (Bansigom Na Publisher, 2025)
The purpose of this study is to use Word Chain game in MA Muhammadiyah UnggulanKota Gorontalo to improve vocabulary mastery of grade X students in English. The background of this study is the low ability of students in mastering vocabulary, which has an impact on other language skills such as reading, writing, speaking, and listening. This study conducted descriptive qualitative research using observation, interview, and documentation as data collection methods. Word Chain game is an interactive learning approach designed to encourage students to be more actively involved in the learning process. The results show that the use of Word Chain can increase students' interest and desire to learn and strengthen their vocabulary mastery in a fun and meaningful situation. This strategy also makes the classroom a healthy place to cooperate and compete. Therefore, the Word Chain game can be used as an effective alternative learning strategy in teaching English at the secondary school level.